Proceedings of the 2000 ACM SIGSOFT International Symposium on Software Testing and Analysis 2000
DOI: 10.1145/347324.348993
|View full text |Cite
|
Sign up to set email alerts
|

jRapture

Abstract: We describe the design of jRapture: a tool for capturing and replaying Java     program executions in the field. jRapture works with Java binaries (byte code) and any compliant implementation of the Java virtual machine. It employs a lightweight, transparent capture process that permits unobtrusive capture of a Java program's executions. jRapture captures interactions between a Java program and the system, including GUI, file, and console inputs, among other types, and on replay it presents each thread wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, this results in very high overheads since each event has to be instrumented. Other approaches [26,47] avoid this low level instrumentation, however they either modify the Java API or require the application to be instrumented with external tools in order to use their custom-developed APIs. CRIU [48] is a checkpoint and restore system based on Linux that is language-agnostic avoiding the overheads and limitations of previous approaches.…”
Section: Related Workmentioning
confidence: 99%
“…However, this results in very high overheads since each event has to be instrumented. Other approaches [26,47] avoid this low level instrumentation, however they either modify the Java API or require the application to be instrumented with external tools in order to use their custom-developed APIs. CRIU [48] is a checkpoint and restore system based on Linux that is language-agnostic avoiding the overheads and limitations of previous approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Monitoring software execution may violate privacy by collecting sensitive data, the monitoring process can be an expensive task for the large scale software and may induce a significant overhead (Chen and Kim 2015;Nayrolles et al 2017;Rößler et al 2013). Tools like ReCrash (Artzi et al 2008), ADDA (Clause and Orso 2007), Bugnet (Narayanasamy et al 2005), jRapture (Steven et al 2000), MoTiF (Gómez et al 2016), Chronicler (Bell et al 2013), and SymCrash (Cao et al 2014) fall in this category.…”
Section: Crash Reproductionmentioning
confidence: 99%
“…To help developers in this process, various automated techniques have been suggested. These techniques typically either use program runtime data (Artzi et al 2008;Clause and Orso 2007;Narayanasamy et al 2005;Steven et al 2000;Gómez et al 2016;Bell et al 2013;Cao et al 2014;Rößler et al 2013) or crash stack traces (Bianchi et al 2017;Soltani et al 2017;Nayrolles et al 2017;Xuan et al 2015;Chen and Kim 2015) to generate a test case that triggers the reported crash.…”
mentioning
confidence: 99%
“…In [1] the authors presented a tool to capture and replay classic desktop Java program executions in the field. In their work they described how all the interactions between the main program and the system are stored, including the GUI displayed.…”
Section: Related Workmentioning
confidence: 99%